Особливості мікроморфологічної будови вегетативних і генеративних органів та компонентний склад ефірних олій Dracocephalum moldavica L. у зв'язку з інтродукцією в Житомирському Поліссі - Kotuk, L.A.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Micromorphological peculiarities of the structure of vegetative and generative organs of Dracocephalum moldavica L. and the component composition of essential oils extracted from them are found. Essential oil containers of D. moldavica are glandular trichomes and essential oil peltatnye glands, localized on all aerial parts of plants: stems, leaves, bracts, calyx and corolla, but their distribution is uneven. The highest density of aromatic peltatnyh glands found on the abaxial surface of the bracts and the adaxial surface of the corolla. There are no peltatnye glands on the abaxial epidermis of the lower lip of calyx and corolla. Glands with the largest diameter are on the abaxial leaf surface and adaxial surface of the lower lip of the corolla, and the lowest are on the stem of the plant. In the composition of essential oils obtained from Dracocephalum moldavica stems, grown under the conditions of Zhytomyr Polissya of Ukraine, — 19 substances, from the leaves — 16, from the flowers — 20 were identified. The high content of nerali (43.49 %) and geraniali (42.45 %) were fixed in the leaves, neroli and geraniol (28.14 and 15.76 %) — in the stems.